2022
DOI: 10.3389/fcdhc.2021.794493
|View full text |Cite
|
Sign up to set email alerts
|

How Do Virtual Visits Compare? Parent Satisfaction With Pediatric Diabetes Telehealth During the COVID-19 Pandemic

Abstract: BackgroundIn response to the COVID-19 pandemic, many countries relaxed restrictions on telemedicine, allowing for a robust transition to virtual visits for routine care. In response, centers rapidly instituted and scaled telemedicine for pediatric diabetes care. Despite numerous center reports on their experience, little is known about parent perspectives on the widespread increase of telemedicine for pediatric diabetes appointments.ObjectiveTo assess parent satisfaction with virtual care for pediatric diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…22 Furthermore, our finding is lower than previous Indian and American studies that documented that more than 90% of the caregivers were satisfied with the quality of service, convenience, and benefits of teleconsultation in Indian 13 and American settings. 3 It was also quite different from the parents' satisfaction (94.2%) observed with pediatric urology telemedicine in American context 12 and the level (80.5%) reported in Italy. 23 The discrepancies in satisfaction profiles across the different settings can be justified by multiple reasons.…”
Section: Factors Associated With Caregivers' Satisfactionmentioning
confidence: 66%
See 1 more Smart Citation
“…22 Furthermore, our finding is lower than previous Indian and American studies that documented that more than 90% of the caregivers were satisfied with the quality of service, convenience, and benefits of teleconsultation in Indian 13 and American settings. 3 It was also quite different from the parents' satisfaction (94.2%) observed with pediatric urology telemedicine in American context 12 and the level (80.5%) reported in Italy. 23 The discrepancies in satisfaction profiles across the different settings can be justified by multiple reasons.…”
Section: Factors Associated With Caregivers' Satisfactionmentioning
confidence: 66%
“…1 The effort to balance the ongoing need for patient care with the risks to patient and staff safety paved a way for a swift transition to virtual visits for routine care. [2][3][4] In practice, the precautions to contain the virus became an opportunity to exploit telemedicine features for clinical care. 5 As such, certain developed nations had nearly nine-fold increment in video visit consultations during the COVID-19 pandemic compared to the same previous period in an American health institution.…”
Section: Introductionmentioning
confidence: 99%
“…Most of included studies ( n = 32) were conducted in United States [ 17 48 ], and a few were conducted in Italy ( n = 3) [ 49 – 51 ], Spain ( n = 2) [ 52 , 53 ], Egypt ( n = 1) [ 54 ], Australia ( n = 1) [ 55 ], India ( n = 1) [ 56 ], United Kingdom ( n = 1) [ 57 ], Canada( n = 1) [ 58 ], France ( n = 1) [ 59 ], Colombia ( n = 1) [ 60 ]. The vast majority included studies ( n = 38) reported on the types of participants’ diseases, which includes head and neck otolaryngology ( n = 1) [ 17 ], pediatric ( n = 1) [ 52 ], physical, occupational, and speech therapy ( n = 1) [ 18 ], orthopaedic ( n = 1) [ 19 ], pediatric pulmonary ( n = 1) [ 20 ], cancer ( n = 4) [ 21 , 30 , 50 , 58 ], neurology ( n = 1) [ 22 ], pediatric urology ( n = 1) [ 24 ], rhinology (n = 1) [ 25 ], neuromuscular disorder ( n = 1) [ 26 ], allergy ( n = 1) [ 27 ], pediatric diabetes ( n = 1) [ 28 ], epilepsy (n = 1) [ 56 ], prechemotherapy ( n = 1) [ 29 ], pediatric rheumatology ( n = 1) [ 32 ], neurosurgery (n = 1) [ 33 ], cystic fibrosis ( n = 1) [ 35 ], pediatric and young adult type 1 diabetes ( n = 1) [ 49 ], shoulder arthroscopy ( n = 1) [ 36 ], pediatric surgery ( n = 1) [ 53 ], vascular surgery ( n = 1) [ 57 ], maternal mental health and substance use disorder treatment ( n = 1) [ 38 ], referral ( n = 1) [ 39 ], dermatology ( n = 1) [ 40 ], endovascular neurosurgery ( n = 1) [ 41 ], gynecologic cancer ( n = 1) [ 42 ], orthopedic ( ...…”
Section: Resultsmentioning
confidence: 99%
“…While the remaining studies ( n = 6) did not limit the patient types [ 23 , 31 , 34 , 37 , 54 , 55 ]. For the evaluation questionnaire, there are part of studies ( n = 16) using existing questionnaires [ 17 , 22 , 26 , 28 , 30 , 32 34 , 42 , 46 , 47 , 50 , 55 , 56 , 58 , 59 ], a few of studies’ questionnaire ( n = 3) were designed based on different studies [ 21 , 24 , 49 ], several studies ( n = 7) evaluating by self-developed questionnaires [ 19 , 25 , 29 , 39 , 51 , 57 , 60 ], and some ( n = 18) studies did not mension the specific questionnaires used [ 18 , 20 , 23 , 27 , 31 , 35 38 , 40 , 41 , 43 45 , 48 , 52 54 ]. In addition, the questionnaires used in several studies ( n = 18) were divided into various dimensions [ 17 , 20 , 23 , 24 , 26 , 32 , 34 , 37 , 38 , 44 , 47 , 49 – 51 , 53 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation